DOES BIG GOVERNMENT HURT GROWTH LESS IN HIGH‐TRUST COUNTRIES?. (12th March 2020) - Bergh, Andreas; Bjørnskov, Christian
Abstract : Social trust is linked to both public sector size and to economic growth, thereby helping to explain how some countries combine high taxes with high levels of economic growth. This paper examines if social trust insulates countries against the negative effects of public sector size on growth, documented in several studies. We note that the effect is theoretically ambiguous. In panel data from 66 countries across 40 years, we find no robust evidence of insulation effects: when excluding countries with uncertain trust scores, our results suggest that big government hurts growth also in high‐trust countries, and that the mechanism is by lowering private investments. ( JEL H10, O11, P16, Z10)